PENINGKATAN GURU MERANCANG PEMBELAJARAN DENGAN PENDEKATAN SAINTIFIK MELALUI KEGIATAN IN HOUSE TRAINING - zubaidah . (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2019)
The pupuse of this research is to improve teacher competency in designing learning with a scientific approach though the implementation of in House Training (IHT) activities in SD Negeri 2 Balng Nisam Semester II in the 2017-2018 academic year. In addition, this study also aims to describe the teacher’s understanding of the scientific approach. This research aschool action research by taking as many as 7 research subjects. The research was carriedout in two cycles of cycles and each consisted of 4 stages, namely: planning, implementation, observation and reflection. The astablished performance indicators ate that if a minimum of 85% of teachers is classified as capable and good in designing learning with scientific approach, then it can be said that the actions implemented are successful.